BSA‐Mediated Synthesis of Bismuth Sulfide Nanotheranostic Agents for Tumor Multimodal Imaging and Thermoradiotherapy. (23rd May 2016) - Wang, Yong; Wu, Yongyou; Liu, Yujing; Shen, Jia; Lv, Ling; Li, Liubing; Yang, Liecheng; Zeng, Jianfeng; Wang, Yangyun; Zhang, Leshuai W.; Li, Zhen; Gao, Mingyuan; et al.
Abstract : Fabrication of ultrasmall single‐component omnipotent nanotheranostic agents integrated with multimodal imaging and multiple therapeutic functions becomes more and more practically relevant but challenging. In this article, sub 10 nm Bi2 S3 biocompatible particles are prepared through a bovine serum albumin (BSA)‐mediated biomineralization process under ambient aqueous conditions. Owing to the ultrasmall size and colloidal stability, the resulting nanoparticles (NPs) present outstanding blood circulation behavior and excellent tumor targeting ability. Toward theranostic applications, the biosafety profile is carefully investigated. In addition, photothermal conversion is characterized for both photoacoustic imaging and photothermal treatment of cancers. Upon radiolabeling, the performance of the resulting particles for SPECT/CT imaging in vivo is also carried out. Additionally, different combinations of treatments are applied for evaluating the performance of the as‐prepared Bi2 S3 NPs in photothermal‐ and radiotherapy of tumors. Due to the remarkable photothermal conversion efficiency and large X‐ray attenuation coefficient, the implanted tumors are completely eradicated through combined therapies, which highlights the potential of BSA‐capped Bi2 S3 NPs as a novel multifunctional nanotheranostic agent. Abstract : BSA‐capped Bi2 S3 NPs are synthesized in aqueous solution via a pH‐mediated biomineralization process for achieving all‐in‐one biocompatible nanoagents for sensitive photoacoustic imaging and SPECT/CT imaging, and enhanced photothermal‐ and radiotherapy of tumors.